2001
DOI: 10.1080/02652030110070030
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of dietary exposure to ochratoxin A in the UK using a duplicate diet approach and analysis of urine and plasma samples

Abstract: The approach to assess exposure to ochratoxin A from the diet by the analysis of human plasma and urine samples has been developed. Composite duplicate diet samples from 50 individuals and corresponding plasma and urine samples were obtained over 30 days. Samples were analysed using sensitive methods capable of measuring ochratoxin A at 0.001 ng g(-1) in food, 0.1 ng ml(-1) in plasma and 0.01 ng ml(-1) in urine. Analysis of the foods indicated ochratoxin A levels contributing to an average intake in the range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
116
1
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(125 citation statements)
references
References 19 publications
5
116
1
3
Order By: Relevance
“…Several studies -in Canada (Frohlich et al 1991, Scott et al 1998, Lebanon (Assaf et al 2004), Japan (Ueno et al 1998), Norway (Skaug 2003), Germany (Gareis et al 2000), northern Spain (Jiménez et al 1998), Italy (Tuscany) (Palli et al 1999) and Tunisia ) -found no difference with age in positive levels of OTA in human blood (adults). However, in a UK dietary exposure study (Gilbert et al 2001), plasma concentrations of OTA did appear to depend on age, with higher levels in 30-44 year-olds compared to <30 year-olds and >45 year-olds and this was significant for a screening sample taken 30 days before the start of the study. However, the amount of OTA consumed in food had no significant relationship with age.…”
Section: Ochratoxin a In Human Blood And Agementioning
confidence: 99%
See 1 more Smart Citation
“…Several studies -in Canada (Frohlich et al 1991, Scott et al 1998, Lebanon (Assaf et al 2004), Japan (Ueno et al 1998), Norway (Skaug 2003), Germany (Gareis et al 2000), northern Spain (Jiménez et al 1998), Italy (Tuscany) (Palli et al 1999) and Tunisia ) -found no difference with age in positive levels of OTA in human blood (adults). However, in a UK dietary exposure study (Gilbert et al 2001), plasma concentrations of OTA did appear to depend on age, with higher levels in 30-44 year-olds compared to <30 year-olds and >45 year-olds and this was significant for a screening sample taken 30 days before the start of the study. However, the amount of OTA consumed in food had no significant relationship with age.…”
Section: Ochratoxin a In Human Blood And Agementioning
confidence: 99%
“…Mean coefficients of variation of 36 and 27% between weeks were noted in analyses of serum from two villages in Bulgaria (Petkova-Bocharova et al 2003). These studies indicate that single analyses are insufficient to determine individual plasma levels and composites should be used (Gilbert et al 2001). On the other hand, four analyses of serum of one person in Switzerland over one year gave the same result (Zimmerli & Dick 1995).…”
Section: Intra-person Variation With Time Of Ochratoxin a Concentratimentioning
confidence: 99%
“…Gilbert et al [12], found a positive correlation between the urinary concentration of OTA and the consumption of OTA, while Munoz et al [13] reported the presence of OTA and its major metabolite ochratoxin alpha (OTα) in 100% of the samples analyzed. OTα which is produced from the hydrolysis of OTA by the gut microflora in the intestine was the major metabolite detected in the urine of rats [14].…”
Section: Introductionmentioning
confidence: 99%
“…Urinary fD þ DG has now been observed in studies from the UK, France, Sweden and China (100) , and independently in Spain and Italy (105,106) , whilst urinary DG was observed in Austrians (103) . All of the mycotoxin biomarker approaches discussed here are summarised in Table 1; ochratoxin A is additionally included for completeness, as the only other mycotoxin for which biomarker development has been reported (107) . Summaries of aflatoxin biomarker surveys are in numerous reviews; here only aflatoxin-albumin biomarkers are presented from studies of West African infants and children (Table 2), as these relate to latter sections of this review.…”
Section: Deoxynivalenolmentioning
confidence: 99%